MILK-DERIVED BIOACTIVE PEPTIDES WITH ANTIOSTEOPOROTIC EFFECT: A MINI REVIEW - Mada, Sanusi Bello; Abaya, Philip Cefas; James, Dorcas Bolanle; Abarshi, Muawiya Musa; Tanko, Muhammad Said (FUDMA JOURNAL OF SCIENCES, 2020)
Postmenopausal osteoporosis is a global health problem characterized by decreased in bone mineral density (BMD) and progressive deterioration of microarchitecture and subsequent increase in bone fragility and susceptibility to fracture.  More than 200 million people suffer from osteoporosis worldwide  with about 8.9 million fractures and the prevalence rate of osteoporosis is expected to increase significantly in the future because of increased in life expectancy and aging population. Milk-derived bioactive peptides from cow, goat, sheep, buffalo, and camel exhibit several potential health promoting effect including antiosteoporosis, antihypertensive, antioxidative, antithrombotic, immunomodulatory and anti-inflammatory effects. Epidemiological and intervention studies have shown that milk and milk-derived peptides prevented bone loss in pre- and postmenopausal women. Moreover, quite a lot of studies have reported that milk-derived bioactive peptides can induce osteoblast cell proliferation, differentiation and also prevented bone loss in osteoporotic rats model. Thus, milk-derived peptides exhibits beneficial effect against bone-related diseases and can be of particular interest towards prevention and management of postmenopausal osteoporosis. Hence, the present review summarizes various studies using ISI, SCOPUS and PubMed indexed journals to elucidate the potential role of milk-derived bioactive peptides with in vitro and in vivo antiosteoporotic property
Keywords: Postmenopausal osteoporosis, Osteoblasts differentiation, Milk-derived peptides, Antiosteoporotic effect, Mechanism of action